2022
DOI: 10.3389/fendo.2022.1040014
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β-cell hyper-O-GlcNAcylation leads to impaired glucose homeostasis in vivo

Abstract: Protein O-GlcNAcylation is a nutrient and stress-sensitive protein post-translational modification (PTM). The addition of an O-GlcNAc molecule to proteins is catalyzed by O-GlcNAc transferase (OGT), whereas O-GlcNAcase (OGA) enzyme is responsible for removal of this PTM. Previous work showed that OGT is highly expressed in the pancreas, and we demonstrated that hypo-O-GlcNAcylation in β-cells cause severe diabetes in mice. These studies show a direct link between nutrient-sensitive OGT and β-cell health and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…6D). Due to the particular importance of these pathways in nutrient sensing and metabolism of pancreatic islets (49), we further investigated O -GlcNAc protein modification in pancreatic islets. Using an antibody against O -GlcNAc, we found enhanced levels of O -GlcNAc protein modification by immunohistochemistry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6D). Due to the particular importance of these pathways in nutrient sensing and metabolism of pancreatic islets (49), we further investigated O -GlcNAc protein modification in pancreatic islets. Using an antibody against O -GlcNAc, we found enhanced levels of O -GlcNAc protein modification by immunohistochemistry (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This also evidences that OGA is restrictedly increased in ECs but not in other cell types. It has been reported that reduction of protein O -GlcNAcylation in skeletal muscles 59,60 in HFD-fed mice improves glucose tolerance, and OGA deletion in β-cells 61 or oocytes 62 leads to impaired glucose tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstituting Akt signaling and alleviating ER stress in β-cells rescues the phenotype associated with the loss of OGT. Furthermore, abrogating OGA in pancreatic β-cells also leads to impaired glucose homeostasis in vivo [ 217 ]. Thus, balanced expression of OGT and OGA in β-cells is necessary for the proper levels of O -GlcNAcylation.…”
Section: Hbp In Health and Diseasementioning
confidence: 99%